Suicide by unusual methods: a rare case of complex suicide - Sarma, Bedanta; M., Senthil Kumaran; S., Arun Kumar; Dash, Shreemanta Kumar (International Journal of Research in Medical Sciences, 2021)
Genital Self-Mutilation (GSM) is usually associated with mental illness. It is considered as the most brutal form of self-harm. Many cases of such self-harm have been described by various authors in different times. However, its existence in absence of any mental illness and using it as a method of suicide is a matter of question. Although, some cases are reported; its incidence is very low. Its association with complex suicide is even much lower. Usually, in complex suicide, the victim chooses some methods which are less painful. Such a complicated case of complex suicide was brought to the tertiary care center of Dibrugarh, Assam for post mortem examination. The deceased, a 36 years old male was brought with history of cutting his external genitalia followed by hanging. The case has been described in this paper with relevant review literature.